The Street children of Naga City an investigative study - Paita, Christine Alberto 1978-
The present study is about the situation of streetchildren in Naga City and what the local government and other concerned agencies are doing about it. The researcher particularly aims to find out why the streetchildren are in the streets and what factors in the social environment affect the way they perceive and behave in the streets. The seven streetchildren introduced in this study are only a sample of the whole population of streetchildren in the city. Their experiences could not speak for the experiences of other streetchildren, but they give us a picture of what happens in a streetchild's life. In their case, their lives illustrate the typical problems that children of poor families encounter. These are the lack of basic needs such as food and clothing, limited access to formal education, deprivation of time for play and leisure i the cae of working children, and physical and mental abuse of children that happens in some of the homes. Of the seven streetchild respondents, only two could be said to have truly run away from their homes because of physical maltreatment from family members. One of the respondents, who was physically maltreated by the persons who took him in on separate occassions, ran away from home because he was already orphaned. One respondent got lost and did not stay for more than a day in the streets because he was taken to Lingap Center by a barangay official. The rest did not experience physical abuse but the pressure to earn a living for their families. Two streetchildren from the Lingap Center ran away and was taken back to the center. They ran away because one of them was accused by his fellow resident of taking money, while the other one was just pressured into coming with him. The situation of streetchildren in Naga City is being addressed by the local government through its own programs and its social welfare arm - the CSWD, and in coordination with the different non-government organizations, one of which is the Bicol Organization for Youth Services, or the BOYs Foundation, and other concerned groups, agencies, and institutions in the city. The City Social Welfare and Development Office, as the devolved unit of the local government of Naga City, is tasked to look after the welfare of children in Naga. Their particular concern with regard to streetchildren is to reunite them with their families. If these children are already abandoned, the CSWD refers them to Lingap Center, a temporary shelter for homeless and neglected children. These two social welfare units, along with NGOs, are the primary supervising forces that are after the welfare of streetchildren in Naga City.